Patients’ Experiences with Specialist Care via Video Consultation in Primary Healthcare in Rural Areas - Annette M. Johansson; Inger Lindberg; Siv Söderberg (International Journal of Telemedicine and Applications)
Introduction. Video consultation (VC) can improve access to specialist care, especially for individuals who live in rural areas that are long distances from specialist clinics. Aim. The aim of this study was to describe patients’ experiences with specialist care via VC encounters. Method. Interviews were conducted with 26 patients who had participated in a VC encounter. The data were analysed using thematic content analysis. Result. The analysis resulted in two themes. The theme “confident with the technology” was constructed from the categories “possibilities and obstacles in using VC encounters” and “advantages and disadvantages of the technology.” The theme “personal satisfaction with the VC encounters” was constructed from the categories “support from the healthcare personnel,” “perceived security,” and “satisfaction with the specialist consultation.” Conclusion. The patients who did not think that the VC was the best care still considered that the visit was adequate because they did not have to travel. An important finding was that the patients’ perceived even short distances to specialty care as expensive journeys because many patients had low incomes. Among the patients who had more than one VC, the second encounter was perceived as safer. Additionally, good communication was essential for the patient’s perception of security during the VC encounter.